2014
DOI: 10.1371/journal.pone.0089595
|View full text |Cite
|
Sign up to set email alerts
|

Human Adipose Tissue-Derived Stromal/Stem Cells Promote Migration and Early Metastasis of Triple Negative Breast Cancer Xenografts

Abstract: BackgroundFat grafting is used to restore breast defects after surgical resection of breast tumors. Supplementing fat grafts with adipose tissue-derived stromal/stem cells (ASCs) is proposed to improve the regenerative/restorative ability of the graft and retention. However, long term safety for ASC grafting in proximity of residual breast cancer cells is unknown. The objective of this study was to determine the impact of human ASCs derived from abdominal lipoaspirates of three donors, on a human breast cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
119
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(125 citation statements)
references
References 59 publications
5
119
0
1
Order By: Relevance
“…All studies included in this review were published in English or had an expanded abstract in English. Investigations that used mixed animal and human cells in vivo were included, for example, those using human ASCs in mice to study tumor behavior (38,39). Special attention was given to peer-reviewed articles that explicitly addressed the relationship between human cancer development, growth, metastasis, and ASCs.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…All studies included in this review were published in English or had an expanded abstract in English. Investigations that used mixed animal and human cells in vivo were included, for example, those using human ASCs in mice to study tumor behavior (38,39). Special attention was given to peer-reviewed articles that explicitly addressed the relationship between human cancer development, growth, metastasis, and ASCs.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…17,28 Recently, Rowan et al found significantly increased multiorgan spreading of MDA tumors and partial epithelialto-mesenchymal transition after local addition of human adipose-derived mesenchymal stromal cells; however, in contrast to earlier reports, they found no increase of breast cancer cell growth. 16 In our study, we could demonstrate dose-dependent effects, which may have a high impact on the clinical scenario.…”
Section: Discussionmentioning
confidence: 62%
“…[8][9][10] Because of these functionalities, local and migrating stem cells have been suspected to endorse breast cancer development. 11,12 Suggested by reports, adipose-derived mesenchymal stromal cells, and more in general mesenchymal stem cells, can promote progression and metastasis of breast cancer [13][14][15][16][17] through homing of stem cells to tumors as an evident process. [18][19][20] Cytokines and chemokines might play a role in breast cancer growth, 21,22 metastasis, or recurrence, with growing evidence that growth and progression of breast tumors depend on their microenvironment as well.…”
mentioning
confidence: 99%
“…However, numerous studies have demonstrated the anti-proliferative or anti-tumorigenic effects of ASCs. For example, preconditioned endothelial progenitor cells have been observed to reduce melanoma metastasis by cell-cell interactions induced by secreted protein, acidic and rich in cysteine, as well as endocytosis (9). Human ESCs have been reported to secrete soluble factors that arrest the growth of human epithelial cancer cell lines (10).…”
Section: Ink4amentioning
confidence: 99%
“…A similar tumorigenic effect was observed in human prostate (6) and breast (7) cancer cells in mice. Furthermore, co-culture of ASCs enhanced the proliferation of human squamous cell carcinoma cells (8) and the migration of breast cancer cells in a xenograft model (9). However, conversely, numerous studies have reported suppressive effects of ASCs on tumorigenesis.…”
Section: Introductionmentioning
confidence: 98%